3D finite element modeling of water diffusion behavior of jute/PLA composite based on X-ray computed tomography. (20th October 2020) - Jiang, Ning; Li, Yaomin; Li, Di; Yu, Tao; Li, Yan; Xu, Jiachuan; Li, Ning; Marrow, Thomas James
Abstract: A three-dimensional (3D) finite element (FE) modeling approach, which includes the true internal microstructure of short plant fibre reinforced composites, is proposed to accurately simulate water diffusion behavior. The volume fraction, dimension and orientation distribution of jute fibres in a jute/PLA composite were acquired by segmentation of X-ray computed tomographs (XCT). Surface meshes of the jute fibre and PLA matrix were imported into Abaqus Finite Element (FE) software to establish a 3D model that was used to simulate water diffusion behavior at 23 °C. The results were in good agreement with experimental measurements. Graphical abstract: Image 1